WRITING THE SIMILAR GOSPELS - Mansour, Al-Bahloul Ali; Idris, Mohamed Razaq; Ben Ismail, Ahmed Manawar; Ben-Yacoub, Tho Al Azaaim (Journal of Humanities & Social Sciences, 2018)
The history of religions still represents a fertile research topic for studies because of the breadth of its matters, and its extension through the history. It is the topic of the current study in three of the New Testament. The Almighty, Allah, has provided His Prophet Jesus peace be upon with the Bible, and sent him to his people, the Children of Israel to guide them to the true religion, and deny whatever directives made by their Rabbis and their interpretations. This Gospel was dined by them and replaced by other gospels which were attributed to people, of whom are those who are doubted in attributing the Gospel to themselves. Therefore, the present study deals with attributing each Gospel of the three Gospels to its writer and verifying its true writer. It also examines the relationships among these Gospels and to the Gospel of Jesus. It is a desk study that is based on collection of scientific data from references, the first of which are the three Gospels. In order to achieve the aims of the study, examine the detailed matters of the study and analyze them as well as obtain results, the study employed a descriptive historical and analytical approach. This was to address the research issues and detect the truth in attributing each Gospel to its writer, and their relationship to Divine Revelation and uncover the truth of these Gospels as sacred Testament among the followers of the Christian religion. The study revealed that the three similar Gospels have no conclusive evidence that they are related to Divine Revelation because they lack frequency condition and the loss of the original Gospels.
Keywords: Gospel; Matthew; Mark; Luke; Writing; New Testament